2023
DOI: 10.3389/fenvs.2022.1039668
|View full text |Cite
|
Sign up to set email alerts
|

The impact of temperature on labor productivity——evidence from temperature-sensitive enterprises

Abstract: Climate change increases the frequency of extreme climate events and impacts the economy and the society in a negative way. As typical climate events, temperature anomalies affect individual health and working conditions, particularly for industries that depend heavily on temperatures. Using a research setting of Chinese temperature-sensitive enterprises, we analyze the impact of temperature on labor productivity. The findings indicate an inverse U-shaped relationship between temperature and labor productivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Furthermore, the impact of climate or weather also significantly impacts construction project materials or labor resources. Ismail et al [63] and Zhang et al [64] concluded that it can be empirically proven that environmental factors such as temperature and relative humidity have a significant impact on workers' performance, whereas Amadi [65] claimed that the meteorological profile of wet-humid climates induces a significantly high percentage of the variance in the real-time demand for bagged cement on construction sites, which reveals that the issue should also be evaluated from a different perspective in terms of activity-specific material demand and supply. This should be one of the results of the duration and cost variability of construction activities during different periods.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the impact of climate or weather also significantly impacts construction project materials or labor resources. Ismail et al [63] and Zhang et al [64] concluded that it can be empirically proven that environmental factors such as temperature and relative humidity have a significant impact on workers' performance, whereas Amadi [65] claimed that the meteorological profile of wet-humid climates induces a significantly high percentage of the variance in the real-time demand for bagged cement on construction sites, which reveals that the issue should also be evaluated from a different perspective in terms of activity-specific material demand and supply. This should be one of the results of the duration and cost variability of construction activities during different periods.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, work environments and productivity are also profoundly influenced by the weather. Certain professions, such as those involving outdoor labor or exposure to extreme temperatures, require meticulous monitoring of weather patterns [22][23][24]. For instance, workers in hot climates must take precautions to avoid heatstroke, while those facing rainy spells may need to adjust their workflows accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…Temperatures below 0 ℃ can cause unprotected water pipes and soil to freeze, affecting excavation and water supply operations in the construction industry; the reinforced concrete in the structure process below -20 ℃ is easy to be brittle, resulting in delayed start or failure of mechanical equipment, affecting the progress of the project. Zhang et al (2023) [12], in using the data of construction enterprises in 31 provinces of mainland China from 2006 to 2019 on the impact of temperature on labor productivity, pointed out that long-term exposure to low temperature environment will reduce tactile discrimination ability and significantly reduce limb operational flexibility, thus reducing labor productivity. When the temperature has an impact on building construction, the construction process of construction enterprises is more sensitive to low temperature than high temperature weather (Fan et al, 2023) [13].…”
Section: Theoretical Analysis and Research Hypothesesmentioning
confidence: 99%